Coping e bem-estar psicológico de cuidadores familiares de crianças com transtorno do espectro autista - Matta, Ina dos Anjos da (2023)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder, and its diagnosis within the family implies a series of changes in plans and routines. These changes can lead to factors that contribute to the experience of parental stress. Faced with stressors related to the care of a child with ASD and potential indicators of parental stress, the coping process is activated to facilitate adaptation and promote the psychological well-being of family caregivers. The aim of this research was to investigate parental stress, coping with stressors related to the care of a child with ASD, and the psychological well-being of family caregivers. This was a crosssectional, descriptive, and analytical study with a quantitative approach. The study included 30 family caregivers whose children with ASD receive assistance from a non-profit institution dedicated to the rehabilitation of children, adolescents, and adults with disabilities, located in the municipality of Anchieta, in the state of Espírito Santo, Brazil. Self-report instruments were used to measure parental stress (Parental Stress Scale [PSS]), coping (Coping Scale), and psychological well-being (Psychological Well-Being Scale). Caregivers also responded to a questionnaire on socio-demographic data (caregivers and children) and the Vineland-3 Adaptive Behavior Scale to characterize the clinical profile of the child. The data underwent descriptive and inferential statistical analysis, and responses to open-ended questions were subjected to thematic analysis. It was observed that the level of satisfaction with the parental role was higher than indicators of parental stress. The identified coping strategies were predominantly of the adaptive outcome coping type. The most perceived and reported domain of psychological well-being by caregivers was personal growth. Correlation analyses revealed that parental stress was positively and moderately related to coping strategies associated with maladaptive outcomes. A strong negative correlation was observed between parental stress and psychological well-being. Families using coping strategies likely to lead to adaptive outcomes showed a moderate positive correlation with the psychological well-being domains of personal growth and purpose in life. In conclusion, the way caregivers perceive stressors related to caring for a child with ASD and how they cope with these stressors can impact their perception of psychological well-being. The findings of this study could contribute to professionals working with children with ASD, enabling them to consider caregivers' coping repertoire and identify external resources, such as the availability of a support network, in order to preserve their psychological well-being even in the face of caregiving challenges.